SATISFACTION OF PATIENTS USING BPJS ON QUALITY OF SERVICES BAHBIAK COMMUNITY HEALTH CENTER, CITY OF MADYA PEMATANGSIANTAR - Nur Mazdalifah (MEDALION JOURNAL: Medical Research, Nursing, Health and Midwife Participation, 2020)
The increasing demands of the community for the quality of health services, the service function needs to be improved to provide patient satisfaction. Service quality is a form of consumer (patient) assessment of the level of service received and the level of service expected. This study aims to determine patient satisfaction using BPJS on the quality of service at the Bah Biak Public Health Center in Pematangsiantar Municipality. This study used a cross-sectional study design with a population of 1,687 BPJS participant patients and a sample of 94 respondents who were determined by purposive sampling technique by conducting interviews using a questionnaire. The results showed that there is patient satisfaction using BPJS based on physical evidence with patient satisfaction (p value = 0.024), there is patient satisfaction using BPJS based on reliability and patient satisfaction (p value = 0.002), there is a relationship between patient satisfaction using BPJS based on responsiveness and patient satisfaction (p value = 0.043), and there is no patient satisfaction using BPJS based on guarantees, empathy with satisfaction which patients (p value > α 0.05). It is recommended for the Bah Biak Pematangsiantar Health Center to further improve the quality of BPJS Health services so that patients are satisfied with the services provided.